Green Tourism: New Economic Opportunities in the Sustainable Era in Ubud Bali - Heriani, Heriani; Purnama, Rahmad (SAINTIS Publishing, 2025)
Green tourism, which emphasizes sustainability and environmental maintenance, offers a sizable new monetary possibility, particularly in regions like Ubud, Bali. This research investigates the twin function of inexperienced tourism in enhancing local economy improvement and maintaining ecological integrity amidst increasing worldwide ecological consciousness. The research data obtained from mixed-methods technique, which quantitative information from the imperative statistics agency (BPS) and qualitative interviews with local stakeholders, the study reveals that tourism practices, such as ecotourism and community-based total lodging, no longer handiest appeal to environmentally conscious tourists but additionally contribute notably to local earnings and task introduction. The findings suggest that green tourism can increase neighborhoods incomes by up to 35-40%, further reinforcing the necessity for collaboration between policymakers, enterprise players, and groups to foster sustainable practices. but, challenges remain, together with inadequate infrastructure, competition with traditional tourism, and the need for constant coverage assistance. This research emphasizes the ability of green tourism as a pivotal factor of sustainable financial development even as highlighting regions for similar research, particularly the integration of theoretical insights with empirical evidence to optimize green tourism strategies. in the end, this look at advocates for endured innovation and network involvement in growing tourism programs that are each economically useful and environmentally responsible.